2018
DOI: 10.1080/13814788.2018.1515907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical leadership and integrated primary care: A systematic literature review

Abstract: Background: Leaders are needed to address healthcare changes essential for implementation of integrated primary care. What kind of leadership this needs, which professionals should fulfil this role and how these leaders can be supported remains unclear. Objectives: To review the literature on the effectiveness of programmes to support leadership, the relationship between clinical leadership and integrated primary care, and important leadership skills for integrated primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 49 publications
0
59
0
4
Order By: Relevance
“… 2 On a systems level, clinical leadership increases physician engagement and results in advances in healthcare reform, regulation, and patient safety policies. 3 Although there is literature that suggests that clinical leadership empowers physicians and improves patient care, 2 - 6 the process by which clinical leadership is learned is less clear, as there have been no standardized residency curricula or competency-based assessments for leadership development in physicians. 6 - 9 While physicians invest the majority of time during their residency to the acquisition and application of clinical knowledge, their exposure to leadership training is generally lacking; they primarily report learning these critical skills through trial-and-error or observation of faculty in higher positions of power.…”
Section: Introductionmentioning
confidence: 99%
“… 2 On a systems level, clinical leadership increases physician engagement and results in advances in healthcare reform, regulation, and patient safety policies. 3 Although there is literature that suggests that clinical leadership empowers physicians and improves patient care, 2 - 6 the process by which clinical leadership is learned is less clear, as there have been no standardized residency curricula or competency-based assessments for leadership development in physicians. 6 - 9 While physicians invest the majority of time during their residency to the acquisition and application of clinical knowledge, their exposure to leadership training is generally lacking; they primarily report learning these critical skills through trial-and-error or observation of faculty in higher positions of power.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study that explored the role of Norwegian municipalities in managing the GP scheme [1], Bjørnhaug and Skyvulstad concluded that GPs should be led by someone with 'a medical background, good knowledge of GPs' work, and an ability to build good relationships with the GPs'. Nieuwboer et al [17] echo some of these statements in a systematic literature review on the role of leadership in facilitating integrated primary care, which concluded that physicians appear to be the most adequate leaders, because of their hierarchical position in relation to other physicians.…”
Section: Challenges Facing Municipalities' Involvement In Quality Impmentioning
confidence: 98%
“…Nieuwboer et al. [ 17 ] echo some of these statements in a systematic literature review on the role of leadership in facilitating integrated primary care, which concluded that physicians appear to be the most adequate leaders, because of their hierarchical position in relation to other physicians.…”
Section: Challenges Facing Municipalities’ Involvement In Quality Impmentioning
confidence: 99%
“…Leadership recognition of the importance of integration and provision of tangible support and resources are in uential in adoption and implementation of care integration [19][20][21][22][23][24]. Program and clinic partner factors supporting integrated implementation…”
Section: Leadership Supportmentioning
confidence: 99%